2022
DOI: 10.1073/pnas.2117904119
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crispatus Limits Bladder Uropathogenic E. coli Infection by Triggering a Host Type I Interferon Response

Abstract: Many urinary tract infections (UTIs) are recurrent because uropathogens persist within the bladder epithelial cells (BECs) for extended periods between bouts of infection. Because persistent uropathogens are intracellular, they are often refractive to antibiotic treatment. The recent discovery of endogenous Lactobacillus spp. in the bladders of healthy humans raised the question of whether these endogenous bacteria directly or indirectly impact intracellular bacterial burden in the blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Similarly, lactobacilli also have a protective effect against E. coli infection. By the induction of a host IFN-1 response, which in turn increases the production of cathepsin D within lysosomes to kill the pathogen, L. crispatus can alleviate bladder uropathogenic E. coli infection in a mouse model ( Song et al., 2022 ). In mice, serial vaginal inoculation with probiotic L. reuteri gives partial protection against S. agalactiae infections, and this effect is mediated in part by mucosal immunity ( Brokaw et al., 2021 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
“…Similarly, lactobacilli also have a protective effect against E. coli infection. By the induction of a host IFN-1 response, which in turn increases the production of cathepsin D within lysosomes to kill the pathogen, L. crispatus can alleviate bladder uropathogenic E. coli infection in a mouse model ( Song et al., 2022 ). In mice, serial vaginal inoculation with probiotic L. reuteri gives partial protection against S. agalactiae infections, and this effect is mediated in part by mucosal immunity ( Brokaw et al., 2021 ).…”
Section: Probiotic Lactobacilli In the Treatment Of Vaginal Infectionsmentioning
confidence: 99%
“…Lactobacillus may have utility as a probiotic for prevention of device biofilms, and as a therapeutic for urinary tract infection. 2,3 The findings call for investigation of the relationship among antibiotic exposure, dysbiosis of urinary tract and ureteral stent niches, and infection. They underscore the development of novel approaches to treat and prevent device-associated infection without selecting for antibiotic resistance.…”
Section: Reply By Authorsmentioning
confidence: 99%
“…Lactobacillus may have utility as a probiotic for prevention of device biofilms, and as a therapeutic for urinary tract infection. 2,3…”
mentioning
confidence: 99%
“…Acid-producing Lactobacillus species can contribute to keeping pathogenic bacteria unable to survive in a more acidic environment at bay, and thus assume a protective role in the bladder [ 10 ]. Indeed, a recent study found that Lactobacillus in the bladder can protect the host from uropathogenic E. coli infection by triggering type I IFN production [ 31 ]. Price et al found that Lactobacillus in women showed no correlation with various factors such as age but discovered that other genera do differ among age groups; Gardnerella and Escherichia were more commonly found in younger and older women, respectively [ 32 ].…”
Section: Urinary Microbiome In Healthy Individualsmentioning
confidence: 99%